Paradoxes of Management in Culture - Yakupov, Alexander Nikolayevich (Cambridge Scholars Publisher, 1920)
This book discusses the problems associated with the development of musical art and education, with a focus on two interrelated facets of this. The first is the analysis and evaluation of the complex, and often contradictory, situations which occur in the establishment of new institutions of culture and art. The second aspect is represented by recommendations and advice given to young managers preparing themselves to act in a self-motivated manner in these institutions. The book can be used as a study guide for managers' training in higher educational institutions in the areas of art and cultu.